Implementasi Sistem Manajemen Mutu ISO 9001:2015 Pada Pengadilan Agama Manado - Djunaidi, Silvana; Mingkid, Elvie; Kawung, Evelin (JURNAL ILMIAH SOCIETY, 2018)
The Manado Religious Court is a court of first instance within thejudiciary of the Supreme Court ensuring the level of service quality provided tothe public through the implementation of an international standard quality systemthat is ISO 9001: 2015. but in fact the implementation process of this policy hasnot been applied maximally based on the results of Internal audit and externalaudit. This study aims to analyze the causes of policy of ISO 9001: 2015 inManado Religious Court is still constrained on its implementation.Keywords :Implementation, Internal Audit, ISO 9001:2015